Deep Learning Approach in The Merdeka Curriculum to Shape Students' Character Through Islamic Religious Education - Aribah, Lutfina; Aulia, Muhammad Ghozil; bin Baharudin, Muhammad Hazim; Rifkiya, Adiba; Khoiriyah, Dini Rofiatul (Kalijaga Journal of Islamic Religious Education, 2025)
Curriculum changes always go hand in hand with the needs and problems of students. The decline in character building among students has become a major issue. The Merdeka Curriculum offers a new approach through deep learning that emphasizes deep, meaningful, and reflective learning, rather than simply memorizing concepts. The purpose of this study is to identify the strategies used in the application of deep learning in Islamic Religious Education to shape student character. The research method used is library research by reviewing various relevant literature. The results show that deep learning provides space for teachers to integrate Islamic values into the real lives of students through various strategies. With this approach, students not only understand religious concepts cognitively but also internalize religious values in their daily lives. The implementation of deep learning in IRE has proven to be able to create a learning environment that supports the development of positive character in students. Students are accustomed to thinking critically, reflecting on experiences, and connecting Islamic teachings with the challenges of modern life.